Can the Market Recognize the Value of the Corporate Governance Mechanism of Chinese Listed Companies?—Empirical Evidence From COVID-19 - Li, Jianwei; Ma, Yunbiao; Shi, Beibei; Yang, Yi (Frontiers in Public Health, 2022)
This paper studies whether the market can recognize the value of corporate governance mechanisms (ownership structure, board structure, and managerial incentives) of Chinese listed companies. We find that when companies are faced with “black swan” events, such as COVID-19, non-state-owned enterprise are found to be more valuable, that is, the stock price of non-state-owned enterprises are more immune to the negative shocks of COVID-19. For board structure, the arrangement of the duality of chairman and CEO is found to be more valuable and can effectively alleviate the negative shocks of the epidemic on the stock price. For managerial incentives mechanisms, it shows that management shareholding, management compensation, and executive stock options are all effective mechanisms and can better withstand the negative shocks of the COVID-19 epidemic on the stock price of companies. This paper sheds light on the value of corporate governance mechanisms in the Chinese capital market from the perspective of investors, which enriches literature in the field of corporate governance.